2019
DOI: 10.17507/tpls.0904.17
|View full text |Cite
|
Sign up to set email alerts
|

Oman’s General Foundation Programs: Focus on General Education Principles and Standards

Abstract: Contemporary research in education has placed the growing emphasis on general education principles and standards intended for empowering students and developing them as personalities with the related discussions set in different socio-cultural and geographical contexts. This paper explores how principles and standards of general education are integrated and implemented to support students’ development and enhancement of their skills in the context of the foundation program at Sultan Qaboos University in Oman. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…According to reports, in Oman's HEIs, there is much evidence of both global and local cultures. Other research in similar circumstances has reported findings that coincide with those reported in these investigations (Tuzlukova et al, 2019).…”
Section: Internationalization Of Curriculum In Omansupporting
confidence: 91%
“…According to reports, in Oman's HEIs, there is much evidence of both global and local cultures. Other research in similar circumstances has reported findings that coincide with those reported in these investigations (Tuzlukova et al, 2019).…”
Section: Internationalization Of Curriculum In Omansupporting
confidence: 91%
“…Sultan Qaboos university consists of nine faculties, including Arts and Social Sciences, Education, Economics and Political Science, Nursing, law, Medicine and Health Sciences, Physical Sciences, Agriculture and Marine Sciences, and Engineering. The university, which has approximately 17,000 students and 1,000 academicians from 113 different countries, ranks 379th (QS ranking 2020) in the world (Tuzlukova, Inguva, Sancheti, 2019).…”
Section: One Of the Most Important Services Provided By Sultanmentioning
confidence: 99%
“…The choice between the two exams depends on an individual's goals and needs. The learning outcomes of GFPE focus on developing basic language skills (Tuzlukova et al, 2019), while IELTS aims to assess a candidate's ability to use English in academic and professional settings. Accordingly, the learning outcomes of GFPE and IELTS are inconsistent.…”
mentioning
confidence: 99%